Religiosity and Authoritative Parenting Style: Prediction of a Positive Relationship with the Meaningfulness of Student Life - Mujidin Mujidin; Ariesta Muthmainnah (Journal of Educational, Health and Community Psychology, 2022)
This study aimed to describe the relationship between religiosity and authoritative parenting style and the meaningfulness of student life. This study used quantitative tests. It gathers 132 students from the Faculty of Psychology of Universitas Ahmad Dahlan with an age range of 18 to 25 years. The sample was collected through proportional cluster random sampling with a proportion of 10% of the population. Three scales were used, namely the religiosity scale, authoritative parenting scale, and life meaningfulness scale. All data that has been collected was immediately analyzed using SPSS version 20. To test the hypotheses of this study, multiple linear regression analysis was used to determine the effect and the extent to which religiosity and authoritative parenting style contribute to life meaningfulness. All hypotheses were shown to be significant starting from the finding of a significant relationship between religiosity and life meaningfulness. Furthermore, there is a significant relationship between an authoritative parenting style and life meaningfulness. Life meaningfulness is achieved by recognizing and understanding God and then acting or behaving according to His words. Religiosity reflects the personality and early family upbringing. The authoritative parenting style applied during childhood may well continue until college. Religiosity and an authoritative parenting style may encourage an individual to make sense of every process, problem, sadness, or happiness and learn to be a better person. Life meaningfulness is correlated positively with religiosity and authoritative parenting style. This independent variable describes religiosity as consistently appreciating and bringing oneself closer to God and authoritative parents as being able to foster individual awareness to perceive the condition in accordance with appropriate understanding and action.Keyword: religiosity, authoritative parenting, positive relationship, meaningfulness